A Vocational Rehabilitation Index and Return to Work after Compensable Occupational Injuries in Australia. Issue 2 (9th January 2018) - Athanasou, James A.
Abstract : This study examined the personal factors as measured by the Vocational Rehabilitation Index and their influence on returning to work after compensable occupational injuries. The participants comprised 462 patients (335 males; 127 females) who underwent a vocational assessment. The length of time since the injury occurred varied from less than 1 year to 15 years with a mean of 3 years (SD = 2). Results indicated that only 23% had returned to work. Just on 30% of the patients had not worked at all since the accident and some 48% had returned to work but were now not working. The major influences on return to work following an occupational injury that were statistically significant ( p < 0.001) were (a) the length of treatment (i.e., time since the injury), and (b) whether there was a psychological problem. The findings support the validity of the Vocational Rehabilitation Index for predicting the probability of return to work following an accident.